Local Governance and Bureaucratic Reform in Public Policy Perspective: What and How? - Cahyono, Anang Sugeng (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze the relationship between local governance and bureaucratic reform from a public policy perspective, focusing on the fundamental questions of what constitutes reform and how it is effectively implemented at the local level. Employing a descriptive qualitative method through literature review and case studies in selected regional governments in Indonesia, this research finds that the success of bureaucratic reform at the local level is strongly influenced by adaptive leadership, active public participation, and institutional capacity to build transparent and accountable systems. The novelty of this study lies in the integration of good governance principles with bureaucratic reform frameworks as a unified approach to improving public sector performance in local governance. Furthermore, this research identifies structural barriers such as weak political will, resistance from bureaucratic actors, and the misalignment between national policies and local needs. The study recommends a contextual approach in designing and implementing bureaucratic reform policies at the local level, including institutional capacity-building, improved vertical and horizontal coordination among government agencies, and enhanced civic engagement in policy supervision and evaluation. The findings contribute theoretically and practically to the discourse on democratic local governance and sustainable bureaucratic reform within the framework of public policy.